Isolation Enhancement Based on TM010 and TE30 Mode Characteristics in a Patch Antennas Using Genetic Algorithm Optimization for Ku-Band Applications - Muddineni Raveendra; U. Saravanakumar; P. Padmaloshani; P. Saam Prasanth Dheeraj; Anand Anbalagan; R. Sreelakshmy (International Journal of Antennas and Propagation)
This paper proposes a novel technique to enhance isolation in rectangular patch antennas by leveraging the mode characteristics of TM010 and TE30 to achieve better than −40 dB between the transmitter and receiver with dual-polarization features. The primary innovation of this work lies in achieving significant isolation enhancement solely by combining two resonant modes with orthogonal polarizations, without incorporating any additional design elements such as parasitic components or decoupling structures. To validate the isolation enhancement based on these mode characteristics, a pair of rectangular transmitter and receiver patch antennas was designed to operate in the frequency range from 14 to 14.25 GHz. The transmitter antenna was designed using the TM010 mode with horizontal polarization, while the receiver antenna used the TE30 mode with vertical polarization. The design utilized a Rogers 3003 series dielectric substrate with a dielectric constant of 3.3 and a loss tangent of 0.003. A genetic algorithm with tournament selection and a multiobjective function was applied to optimize key performance metrics, such as impedance matching, bandwidth, and gain. Following successful optimization, the simulated results were validated against measurements, showing excellent agreement and confirming the accuracy of the proposed antenna design.